Conference The development of a digital cultural heritage eco-system (diségno, 2019)
Following a twenty-year tradition, March in Ferrara is dedicated to the themes of Restoration and Cultural Heritage: three days of conferences, exhibitions, debates and working tables in an event that precedes the contents of the XXVI Salone del Restauro, dei Musei e delle Imprese Culturali, this year scheduled on September, 18th, 19th and 20th. In the framework of palazzo Tassoni Estense, numerous moments of discussion were proposed on the themes of restoration, architectural heritage, design, research and governance of the territories, with particular attention to the Emilia territory affected by the seismic events of 2012. (read more)